Effects of supercritical CO2 adsorption on the mechanical characteristics and failure mechanisms of shale. (15th April 2019) - Feng, Gan; Kang, Yong; Sun, Ze-dong; Wang, Xiao-chuan; Hu, Yao-qing
Abstract: This paper investigates variation in the failure behavior of shale in a ScCO2 -immersion environment with different adsorption periods and layering orientations. Eight types of specimens are investigated, where the inclination of the layering to the applied force θ is 0°, 15°, 30°, 45°, 60°, 75°, 90°, and Divider type. The period of immersion ranges up to 60 days. The results indicate that after 60 days of ScCO2 adsorption, the Brazilian splitting strength ( BSS ), splitting modulus ( E ) and absorbed energy ( U ) of the shale were reduced by 46%, 22% and 50%, respectively, versus those of samples in which there was no adsorption. The root cause of this mechanical weakening is that damage done to the shale by ScCO2 results in the formation of a fragmented structure. Not only tensile failure but also shear failure occurs, making the failure mixed-mode. The mechanical properties of shale show clear changes with θ . Samples with no adsorption, 10-day adsorption, 30-day adsorption and 60-day adsorption show basically consistent change trends with inclination angle ( θ ). Highlights: The influence of ScCO2 adsorption on the failure behavior of shale is investigated. Properties considered: BSS, E, U, and fracture trace. ScCO2 adsorption for 60 days was observed to reduce BSS by 46%, E by 22%, and U by 50%. Fragmentation is the root cause of deterioration in the mechanical properties of shale.